(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the payment system as a key element of the financial infrastructure that ensures efficient money circulation amid the growing share of cashless transactions. It is shown that the speed, reliability, and security of payments depend on the technological development of infrastructure, the centralization of transaction processing, the harmonization of interbank settlements, and the standardization of financial messaging. The article substantiates the need for strategic improvement of the payment infrastructure to maintain the continuity of money flows and the resilience of money circulation.